SYNTHESIS OF POLYETHYLENE OXIDE (PEO)–CHITOSAN HYDROGEL PREPARED BY GAMMA RADIATION TECHNIQUE - Erizal Erizal; Thamrin Wikanta (Indonesian Journal of Chemistry, 2011)
Crosslinked PEO hydrogel containing chitosan for wound dressing has been prepared by gamma radiation technique. Chitosan solutions with different concentration (0.5-2% w/v) have been blended with 5% aqueous solution of PEO and irradiated at the doses 20-40 kGy by gamma rays. The copolymers were characterized by Fourier transform infra red spectroscopy and their physico-chemical properties of hydrogels were evaluated in terms of gel fraction, swelling ratio, elongation at break and antimicrobial activities. It was found that under maximum condition of incorporation 1% chitosan with irradiation dose of 20 kGy, PEO-chitosan hydrogels with high gel fraction (85%), swelling ratio (10 g/g) and elongation at break (145%) were obtained. The examination of the microbe penetration shows that the prepared hydrogels can be considered as a good barrier against microbes. Thus, PEO-chitosan hydrogel showed satisfactory properties for use as a wound dressing.